Non-performing loans and macroeconomic variables in Malaysia: recent evidence - Kepli, Syazwani; Bani, Yasmin; Rosland, Anitha; Laila, Nisful (Fakulti Ekonomi dan Pengurusan, Universiti Putra Malaysia, 2021)
Financial institutions like commercial banks play important role in the financial system by helping countries to grow and provide capital and platform for investors. However, banks need to be able to generate income in their lending business and perform efficiently. Nonperforming loans (NPLs) is one of the tools to determine the efficiency of lending institutions in which reflect the quality of the credit portfolio as well as the health of the banking sector. High levels of NPLs in the banking system places the banks in risky situation which may lead to limited financial activities and consequently lower investment and growth. Motivated by this scenario, this study examines the determinants of NPLs in the Malaysian banking system. Using annual data from 1988 to 2018, the study estimates the short and long-run dynamics of several determinants using the Auto-Regressive Distribution Lag (ARDL) cointegration approach. The empirical results demonstrate mixed results. In the long-run, exchange rate is positive and significantly related to non-performing loans, while industrial production and money supply are negative and significant. However, inflation does not have significant effect on NPLs in Malaysia. The findings of this study is useful in assisting the banking institutions and policy makers to design macro and fiscal policies.